The role of design thinking in managing organizational change - Subaciute, Erika; Rao, Janaki Raghavendra (My University, 2019)
The concept of change management is gaining increased attention both academically and in organizations, due to the complex and dynamic environment in which they work. Organizations must be vigilant to variations in their ecosystem and respond appropriately. Sometimes organizations embark on a change journey and proactively seek to innovate. There is a significant difference today in perceiving the change phenomena as compared to few decades ago. A number of theories and models have evolved to support companies in managing this transition effectively and achieving their intended objectives. While some organizations succeed in their change initiatives, others do not yield the desired result. Some changes result in unintended consequences due to their complexity and disruptive nature. Since the outcome of these changes affect everyone, strategies are needed to overcome these barriers and ensure that the desired objectives are achieved. While some of these strategies are provided in the change management literature and address some of the issues, there is a need to study alternative disciplines since the change is not merely limited to theories and processes. Here, we introduce Design Thinking as that discipline and explore its potential contribution to managing organizational change. The motivation in selecting Design Thinking is due to its increased popularity as a management concept. The salient features of this discipline are empathy, system’s view, prototyping, experimentation and action research which supplements the requirements needed to manage change. This thesis is an effort to explore individually each of these facets of change management and design thinking through a systematic literature review. The findings from this review are synthesized into an analytic framework that depicts how design thinking may support organizations to manage change at strategic and operational levels. The unique contributions of design thinking are a human centered approach through empathy and building innovative capability through facilitating ambidexterity.
Keywords: organizational change management; design thinking, empathy; framework